Social Networks-Budgetary Discipline Linkages in Sub-National Entities - Onyango-Delewa, Paul (Universitas Muhammadiyah Yogyakarta, 2021)
This research intervenes with the seemingly endless empirical debate that seeks explanation to the notorious budgetary discipline problem in the local government. Some scholars attribute it to social networks, but others emphasize entity internal control systems. Supported by budgetary theory-structural equation modeling (SEM) triangulation, the researchers examined data from 33 districts, seven municipalities, and 345 sub-counties in Uganda (East Africa)’s north-western and eastern regions. The SEM results revealed that socio-economic structures and partisan politics are key social network constructs to predict budgetary discipline. However, another attribute, ethnicity, is not. Additionally, the internal control system mediates the social networks-budgetary discipline relationship as initially anticipated. Implications for theory and practice are discussed.